Ergodic theory : advances in dynamical systems - Assani, Idris (Walter de Gruyter GmbH, 2016)
This monograph discusses recent advances in ergodic theory and dynamical systems. As a mixture of survey papers of active research areas and original research papers, this volume attracts young and senior researchers alike.